Patient and stakeholder involvement in resilient healthcare: an interactive research study protocol - Siri Wiig; Karina Aase; Veslemøy Guise; Mary Chambers; Carolyn Canfield (BMJ Open, 2021)
Introduction Resilience in healthcare (RiH) is understood as the capacity of the healthcare system to adapt to challenges and changes at different system levels, to maintain high-quality care. Adaptive capacity is founded in the knowledge, skills and experiences of the people in the system, including patients, family or next of kin, healthcare providers, managers and regulators. In order to learn from and support useful adaptations, research is needed to better understand adaptive capacity and the nature and context of adaptations. This includes research on the actors involved in creating resilient healthcare, and how and in what circumstances different groups of patients and other key healthcare stakeholders enact adaptations that contribute to resilience across all levels of the healthcare system.Methods and analysis This 5-year study applies an interactive design in a two-phased approach to explore and conceptualise patient and stakeholder involvement in resilient healthcare. Study phase 1 is exploratory and will use such data collection methods as literature review, document analysis, interviews and focus groups. Study phase 2 will use a participatory design approach to develop, test and evaluate a conceptual model for patient and stakeholder involvement in RiH. The study will involve patients and other key stakeholders as active participants throughout the research process.Ethics and dissemination The RiH research programme of which this study is a part is approved by the Norwegian Centre for Research Data (No. 864334). Findings will be disseminated through scientific articles, presentations at national and international conferences, through social media and popular press, and by direct engagement with the public, including patient and stakeholder representatives.